The role of literature in shaping cultural identity and social consciousness in contemporary education - Wahyuni, Lilik; Wahyuni, Sri; Mujianto, Gigit; Vinahari, Dessy Kusuma; Melati, Inka Krisma; Jia, Cao (Universitas Muhammadiyah Malang, 2024)
Literature significantly influences cultural identity and social consciousness within contemporary education, particularly regarding Indonesian literary traditions. Globalisation has profoundly impacted education, often resulting in the marginalisation of cultural heritage. This study analyses how literature can preserve cultural values while promoting global awareness and social understanding. The research employs James Paul Gee’s discourse analysis framework to examine texts by notable Indonesian authors, such as Eka Kurniawan, Chairil Anwar, and Seno Gumira Ajidarma, focusing on themes of identity, tradition, and modernity. Data was collected through textual analysis, supplemented by interviews and focus group discussions with educators, literary scholars, and learners. Thematic analysis was utilised to identify key cultural identities and themes related to social issues. The findings reveal that Indonesian literature illustrates significant tensions between tradition and modernity and highlights individual freedom versus societal expectations. Additionally, it offers critical perspectives on the impact of globalisation on cultural identity. The research concludes that integrating literature into educational curricula can enhance learners' appreciation of their cultural heritage, foster critical thinking, and promote multicultural awareness. This approach contributes to a more culturally responsive education system, better equipping learners to navigate the complexities of a globalised world.